Challenged issues faced by Maju Holding for going international / Mohd Nurul Fitrie Zakaria - Zakaria, Mohd Nurul Fitrie (Faculty of Business and Management, 2014)
Internationalization has been debated by numerous studies before regarding the extent of its effectiveness. The primary aim of this study is to explore the issue faced by Maju Holding Sdn Bhd for going international the data collected through questionnaire from 73 respondents was used to test the proposed hypothesis. The survey question designed to determine three elements of issues which include infrastructure, culture and skill. The result reveals there are positive relationships and failed to reject between stated variables. The result of this study surely will benefit the management of Maju Holding to take and realize any necessary development plan due to issue that will faced by them if they choose to be international.